2009
DOI: 10.1016/j.cell.2009.05.026
|View full text |Cite
|
Sign up to set email alerts
|

Telomere Extension Occurs at Most Chromosome Ends and Is Uncoupled from Fill-In in Human Cancer Cells

Abstract: Summary Telomeres are thought to be maintained by the preferential recruitment of telomerase to the shortest telomeres. The extension of the G-rich telomeric strand by telomerase is also believed to be coordinated with the complementary synthesis of the C-strand by the conventional replication machinery. However, we show that under telomere length-maintenance conditions in cancer cells, human telomerase extends most chromosome ends during each S phase and is not preferentially recruited to the shortest telomer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
198
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 216 publications
(212 citation statements)
references
References 45 publications
13
198
1
Order By: Relevance
“…The availability of the 3′ overhang is likely regulated by telomeric structure, for instance the formation of T-loops, whether DNA replication has been completed at the telomere, and the signaling state of the telomere (Doksani et al, 2013; Lee et al, 2015; Tong et al, 2015). A previous report suggested that telomere elongation occurs within 30 min after the completion of DNA replication (Zhao et al, 2009). Given that the replication timing of telomeres is distributed all throughout S-phase (Arnoult et al, 2010), telomerase would be expected to localize to a small subset of telomeres at any given time-point during S-phase.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The availability of the 3′ overhang is likely regulated by telomeric structure, for instance the formation of T-loops, whether DNA replication has been completed at the telomere, and the signaling state of the telomere (Doksani et al, 2013; Lee et al, 2015; Tong et al, 2015). A previous report suggested that telomere elongation occurs within 30 min after the completion of DNA replication (Zhao et al, 2009). Given that the replication timing of telomeres is distributed all throughout S-phase (Arnoult et al, 2010), telomerase would be expected to localize to a small subset of telomeres at any given time-point during S-phase.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the telomerase RNP associates with TCAB1, which facilitates telomerase localization to sub-nuclear structures called Cajal bodies (Venteicher et al, 2009). Human telomerase processively copies telomeric repeats from the template region of TR, adding ~50–60 nucleotides to the single-stranded overhang of most chromosome ends each cell cycle (Schmidt and Cech, 2015; Zhao et al, 2011; 2009). Importantly, telomerase is only present at ~250 copies per cell (Xi and Cech, 2014), an amount comparable to the number of chromosome ends in a cancer cell after DNA replication has occurred.…”
Section: Introductionmentioning
confidence: 99%
“…We estimated the rate of telomere loss to be ~20–30 bp per population doubling, suggesting that SBDS deficiency-induced telomere shortening might be caused by telomerase dysfunction, since ~60 nt are normally added to chromosomal ends by telomerase during each cell division (Zhao et al, 2009, 2011). To test this possibility, we measured total telomerase activities in the SBDS knockdown cells using the telomere repeat amplification protocol (TRAP) assay, but we found no significant differences in whole-cell telomerase activities between control and SBDS knockdown (KD) cells (Figures 1D and 1E).…”
Section: Resultsmentioning
confidence: 99%
“…Techniques have recently been developed that allow investigation of the mode of action (processive or distributive) of telomerase during a single cell cycle. [52][53][54] These studies suggest that in human cancer cells, telomerase extends most telomeres by about 60 nt, and that each end is extended processively by one molecule of telomerase. Using this type of approach, we should be able to determine how telomere cohesion influences telomere elongation by telomerase.…”
Section: Tin2 Hp1 and Sister Telomere Cohesionmentioning
confidence: 99%